An experimental investigation of surface pressures in separated and reattaching flows: effects of freestream turbulence and leading edge geometry. Issue 165 (June 2017) - Shu, Z.R.; Li, Q.S.
Abstract: Flow separation and reattachment over bluff bodies is frequently encountered in a wide range of engineering practice. This study presents an experimental investigation on the characteristics of surface pressures over bluff bodies in separated and reattaching flows, with emphasis placed on the effects of freestream turbulence and leading edge geometry. Measurements of mean, r.m.s and peak suction pressures on blunt flat plates with different leading edge shapes are conducted in both smooth and grid-generated turbulent flows in wind tunnel test, and comparative analyses are carried out to unveil the dependence of the distributions of mean, r.m.s and peak suction pressure coefficients on turbulence intensity, turbulence integral length scale and leading edge geometry. The experimental results show that the distributions of mean pressure coefficient respond strongly to changes of turbulence intensity, but with little effect on turbulence integral length scale except in the leading edge region for the cases there are large differences of the parameter. The distributions of r.m.s and peak suction coefficients demonstrate a close correlation on both the turbulence intensity and integral length scale. In addition, the distributions of surface pressures are also related evidently on the leading edge geometry. The mean reattachment length exhibits a monotonic increase as the leading edge angle increases, while the maximum magnitudes of r.m.s and peak suction pressure coefficients are found to increase with increasing leading edge angle. Highlights: Investigating effects of turbulence on mean, r.m.s and peak suction pressures in separated and reattaching flows. Assessing influences of leading edge geometry on surface pressures on blunt flat plates.